Latas d’água nas cabeças : percepções sobre a água na comunidade quilombola de Mata Cavalo - Amorim, Priscilla Mona de (2017)
This research considered the Quilombola community of Mata Cavalo, located in the municipality of Nossa Senhora do Livramento, Mato Grosso. This community has historically coexisted with several struggles, among them, the search for the definitive title of possession of the land and access to water. We aimed to understand the perception that the Mata Cavalo school community has about nature, especially water, as well as the factors they attribute to the lack of water, as well as the difficulties and conflicts that exist in relation to this natural element. Our research was carried out in the school community of the Tereza Conceição Arruda State School. Our methodological contribution was Cartography of the Imaginary (elaborated by Michèle Sato) that gave us many ways to interpret, valuing all the steps along the way, understanding that research ways are important as what we want to reach. We conducted fieldwork with semi-structured interviews and participatory mapping workshops. Historically, access to water is one of the greatest difficulties faced in the Quilombo, the interviewees perceived the water as something essential to life and indicated that human actions have affected the quality and availability of this natural source. The themes of water and environmental education are worked on a regular basis in the community school, that contributes to the critical education necessary for the Quilombolas, who could have the school as one of the spaces to understand the social and environmental problems experienced daily. The solution unanimously suggested by the Quilombolas for the lack of water is the construction of artesian wells in their backyards, which is justified by the urgency to have access to water and limited access to streams. Most of the wells are located on farmer properties, in areas not yet regularized and indemnified. Because life is essential, environmental education must emphasize this problem faced by the Quilombolas, which weakens them and, together with the neglect of public power, makes them even more vulnerable to racism and environmental injustices.